Acessibilidade web – aplicação de diretrizes e padrões para avaliação e melhoria de portais eletrônicos governamentais - Corado, Daiene Ferreira Silva (Universidade Federal do Tocantins, 2021)
This project aims to implement the analysis of the Web Accessibility of the electronic portals of the Federal Institutions of Higher Education (FIHE) and to propose a guide with orientations focused on continuous adequacy/improvement of the Web Accessibility to the portal of the Federal University of Tocantins (FUT). These tasks will be accomplished through the review of bibliographies that address the topic in question, and through the manual and automatic evaluation of the Web Accessibility of the selected portals. It is expected that the bibliographic survey will provide a more acute perception of the strategies necessary to enhance the use of web spaces by all individuals, regardless of limitations. The results obtained in the analysis of the FIHE electronic portals will be fundamental for the elaboration of the guide with recommendations of Web Accessibility, directed to the UFT portal, which aim to provide an efficient contribution for the university to be able to provide through the portal, services and information increasingly aligned with the values sought by the institution.